Pengaruh Pelaku UMKM Dan Pelatihan Penyusunan Laporan Keuangan Terhadap Pelaporan Keuangan UMKM Berdasarkan SAK EMKM - Wulandari, Thita; Handayani, Desi; Amelia Herman , Lisa (Politeknik Raflesia Press, 2024)
The existence of MSMEs has an influence on the community's economic income. This study seeks to assess how MSME participants and their training impact the preparation of financial reports in accordance with SAK EMKM for MSME financial reporting. This research uses quantitative methods. The data collection method was carried out through distributing questionnaires to respondents. The population in this research is MSMEs located in the Padang City area, with a sample of 110 MSMEs. Samples were obtained using probability sampling methods and sampling techniques were carried out using purpose sampling techniques. The findings of this study reveal that the MSME participant variable significantly affects MSME financial reporting in accordance with SAK EMKM. However, the variable related to training for financial report preparation shows no influence on MSME financial reporting based on SAK EMKM. This study also shows that the variables of MSME actors and training in preparing financial reports together have a significant effect on MSME financial reporting based on SAK EMKM.